GPS Trajectory-Based Spatio-Temporal Variations of Traffic Accessibility under Public Health Emergency Consideration. (23rd March 2021) - Dong, Luqi; Lv, Ying; Sun, Huijun; Zhi, Danyue; Chen, Tingting
Abstract : Medical services are essential to public concerns and living qualities. Facing new public health events, the spatio-temporal variation of healthcare accessibility can be different, which is ignored in the previous accessibility studies. In this paper, we study the spatio-temporal variation of healthcare accessibility and residents' accessibility to the designated hospitals under public health emergencies such as COVID-19. Metropolitan Beijing is chosen as the study area. Then, we analyze the spatial disparity and the temporal variation and measure the matching degree between healthcare accessibility and population density. From the perspective of epidemic prevention, we evaluate the medical capacity of the designated hospitals. The autocorrelation method is used to analyze the spatial correlation of residents' accessibility to designated hospitals in the study area. A conclusion can be drawn that 74.14% grids in the study area have proportionate population density and healthcare accessibility. We find that the 5 th Medical Center has sufficient medical resources, and Puren hospital is less affected by time. Moreover, the result of residents' accessibility to the designated hospitals presents a pattern of high-value aggregation in the arterial road neighborhood. At the same time, the peripheral areas show a trend of low-value aggregation. The research in healthcare accessibility can provide a reference for policymakers in medical service development and public emergency management.